The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1136/pgmj.66.775.356
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and Mycoplasma pneumoniae infection

Abstract: Summary:Anticardiolipin antibody levels were measured in 57 patients with Mycoplasma pneumoniae infection and 21 patients with other infections. Significantly more patients in the mycoplamsa group had increased IgM and IgG anticardiolipin. Within the mycoplasma group significantly higher titres were found in patients with severe infection (assessed by need for hospital admission) and in patients with cold agglutinins. A tendency for particularly high titres to occur in patients with extra-pulmonary complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
(4 reference statements)
3
40
0
1
Order By: Relevance
“…A single case of facial nerve palsy in association with M. pneumoniae infection with production of antiphospholipid antibodies has been reported [Snowden et al, 1990]. This suggests that vasculopathy of the peripheral vessels resulting from the production of these autoantibodies leading to neural damage can be a cause of cranial, and possibly also peripheral, nerve palsies.…”
Section: Facial Nerve Palsymentioning
confidence: 96%
See 3 more Smart Citations
“…A single case of facial nerve palsy in association with M. pneumoniae infection with production of antiphospholipid antibodies has been reported [Snowden et al, 1990]. This suggests that vasculopathy of the peripheral vessels resulting from the production of these autoantibodies leading to neural damage can be a cause of cranial, and possibly also peripheral, nerve palsies.…”
Section: Facial Nerve Palsymentioning
confidence: 96%
“…Stroke can occur in children [Fu et al, 1998;Lee et al, 2009;Leonardi et al, 2005;Ovetchkine et al, 2002;Parker et al, 1981;Tanir et al, 2006;Visudhiphan et al, 1992] as well as in adults [Mulder & Spierings, 1987;Padovan et al, 2001;Senda et al, 2010;Snowden et al, 1990;Sočan et al, 2001;Sotgiu et al, 2003]. The middle cerebral arteries are most often affected [Fu et al, 1998;Leonardi et al, 2005;Mulder & Spierings, 1987;Parker et al, 1981;Senda et al, 2010;Sotgiu et al, 2003], though the internal carotid arteries are affected in a few cases Tanir et al, 2006;Visudhiphan et al, 1992].…”
Section: Strokementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many clinical criteria for APS have also been well documented in patients with M. pneumoniae infection, including Guillain-Barré-like illness and other central nervous system manifestations, hemolytic anemia, positive Coombs test, thrombocytopenia, and arthritis. [Asherson et al, 1994;Snowden et al, 1990;Yáñez et al, 1999].  Snowden et al (1990) found antiphospholipid antibodies in more than 50% of patients with M. pneumoniae pneumonia, especially those with severe infections requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%